Interest In Participating Brevet Training: Motivation And Knowledge As Determinants Of Accounting Students In East Kalimantan - Kusno, Hendra Sanjaya; Santika, Sisca; Ramadhani, Ranita; Sari, Danar Retno; Arazy, Dito Rozaqi (E-Jurnal Akuntansi, 2026)
This study aims to reveal the role of economic motivation as a moderating variable that can strengthen the relationship between career motivation, quality motivation, and knowledge on the interest of Accounting students in East Kalimantan in participating in the Tax Brevet training program. The study utilized secondary data with a population of Accounting students in East Kalimantan selected through accidental sampling. Career motivation, quality motivation, and tax knowledge have an influence on student interest in participating in the Tax Brevet training program. Economic motivation can only strengthen the relationship between quality motivation and interest in participating in the tax brevet, but not on career motivation or tax knowledge.